Is there an association between alpha 2-Heremans-Schmid glycoprotein (AHSG) gene Thr256Ser polymorphisms with aortic calcification in regular hemodialysis patients in Medan, Indonesia - Riri Andri Muzasti; Dr Suhardjono; Bambang Purwanto; Juwita Sembiring Rosita (Medicinski glasnik, 2019)
Aim: Alpha2-Heremans-Schmid glycoprotein (AHSG), a circulating plasma protein, plays an essential role in bone and vascular mineralization. The impact of AHSG gene polymorphisms on aortic calcification in haemodialysis patients was inconsistent. We performed this study to clarify precise association among AHSG gene Thr256Ser single-nucleotide polymorphisms and aortic calcification. Methods: Patients on stable regular haemodialysis treatment for more than thirty months were included in a cross-sectional study at Rasyida Renal Hospital Medan. Lateral spine X-rays were performed to evaluate the aortic calcification. Genotyping for the polymorphisms was carried out using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) techniques. Results: Aortic calcification was detected in 69.8% of patients. From 106 patients, 49 patients (46.2 %) had CC (Thr/Thr), 54 (51.0%) had CG (Thr/Ser) and three (2.8%) patients had GG (Ser/ Ser) polymorphism. The proportion of patients with heterozygous or homozygous G allele (CG and GG genotypes) is more likely (91.2%) to have aortic calcification. The bivariate analysis showed that Thr256Ser polymorphism (G allele) was associated with increased risk for aortic calcification (PR = 2.03; 95% CI 1.48-2.80; p<0.001). However, overall results from multivariate analysis showed that Fetuin-A level <204 pg/mL (PR = 22.0; 95% CI 3.32-145.91; p=0.001) and IL-6 level ?53.05 mg/dL (PR = 19.50; 95% CI 2.87-132.41; p=0.002) were the major risk factors for the occurrence of aortic calcification. Conclusion: AHSG Thr256Ser gene polymorphism showed an association with aortic calcification in regular haemodialysis patients, but Fetuin-A and IL-6 have a dominant role in the development of aortic calcification.
Keywords: alpha-2-HS-glycoprotein; vascular calcification; haemodialysis